Structural effect of SWCNTs grown by PECVD towards NH3 gas sensing and field emission properties. (November 2019) - Lone, Mohd Yaseen; Kumar, Avshish; Ansari, Nagma; Husain, Samina; Zulfequar, Mohammad; Singh, Ravi Chand; Husain, Mushahid
Graphical abstract: Fig. Ammonia Gas Sensor and Field Emission modal with obtained Respective Results Highlights: Long network of RO-SWCNTs and VA-SWCNTs were separately grown by PECVD technique. The electron microscopes have revealed the uniform and high quality structures of as grown SWCNTs. VA-SWCNTs and RO-SWCNTs based sensors were fabricated for gas sensing studies. The field emission studies of VA-SWCNTs and RO-SWCNTs were also performed using diode set up. VA-SWCNTs were observed to be best for FEDs whereas RO-SWCNTs were observed to be excellent for gas sensors. Abstract: Vertically aligned single wall carbon nanotubes (VA-SWCNTs) and randomly oriented (RO) SWCNTs have been successfully grown on Silicon (Si) substrate at an operating temperature of 650°C by plasma enhanced chemical vapour deposition (PECVD) technique. In the present work, two sets of sensors (RO-SWCNTs & VA-SWCNTs) were fabricated. An excellent enhancement in sensor response about 200–250% was achieved by RO-SWCNTs sensor while for VA-SWCNTs sensor, it was observed to be 80–100% at constant concentration of NH3 (40 ppm) and at a temperature of 40°C. Fast response/recovery time characteristics with accurate repeatability and long term stability were observed in sensitivity. It was also observed that as-fabricated sensors are more selective towards NH3 . In field emission studies, field enhancement factor 1.2 × 10 4 at turn on voltage 2.8 V/μm and with current density 3 mA/cm 2 was measured by VA-SWCNTs while for RO-SWCNTs the field enhancement factor was calculated 3.8 × 10 3 at turn-on voltage 4 V/μm with current density 1.7 mA/cm 2 .